Dimensão político-social da comunicação entre adolescentes e enfermeiros no pré-natal - Gonçalves, Tuany Petúnia Carvalho (2018)
The objective of this study was to analyze the sociopolitical dimension of communication between pregnant adolescents and nursing care situations in the contexto of Family Health Strategy to evidence the social meanings of the discourses they both mobilize, the places they occupy in the interrelationship and the strategies they use in the symbolic fight to make themselves recognized. Every communicational process is politico-social. It is an action that mobilizes discourses and senses constructed by people and their communities, from various sources and social voices, as it involves/shares negotiation and/or imposition of meanings among those involved, as part of the fight for the predominance of the senses that carry and represent. In this process, the participants occupy changing symbolic positions, of greater, of equal or lesser power, for which they develop strategies according to social interests. The qualitative study, was performed between march and december 2016 in two units of Family Health Strategy, was performed through participant observation of the prenatal meetings between nurses and 21 pregnant adolescents, and individual interviews. The analysis of the empirical was based on the analytical categories communication and symbolic market, discussed by Inesita Araújo, and discursive practice, senses, ideology, hegemony and power of the Critical Discourse Analysis. The nurse's discourse is composed, above all, of fragments of biomedical technical-scientific knowledge and common-sense knowledge, built up in her experiences and in contact with the media that convey ideas about healthy behaviors in health. Adolescents also express knowledges built from the biomedical discourse, on the basis of which they understand prenatal care as a space for verification of the baby's health and the physical health of their pregnancy. There were divergent meanings regarding pregnancy in adolescence, while the nurses consider that this is not the right moment, the adolescents perceive this experience as positive. It was also evidenced that the communicational model in prenatal care is characterized by strong directivity of the nurse, and by a mechanical, informational and repetitive way of communicating, on a heteronomous and nonspecific basis. The professional occupies, almost permanently, a central place in the interlocution and of greater power. For this, several strategies of control are used to keep the adolescents in a peripheral position: it raises the tone of voice, interrupts them, recriminates them, etc. Adolescents, in turn, seem passive in the face of the imposed communication model, however, try to make themselves recognized and the issues they bring, through strategies such as questioning and self-defense of behavior. Being silent reveals a defense mechanism, assumed by fear and refusal to put herself in a situation of possible judgment and censorship, in which there is inequality of power. In the analyzed practice, there is a strong presence of relations of domination and delegitimation of the discourse and the senses of the adolescents and this symbolic power disparate compromises the health care, since it reinforces what they can be and exercise, and the social space that they can occupy, reinforcing the established social inequalities of participation, opportunities and rights.